IS IT TIME FOR MALAWI TO CHANGE ITS ECONOMIC GROWTH ENGINE? EVIDENCE FROM NEW STRUCTURAL ECONOMICS - Kiru Sichoongwe (Journal of Management Small and Medium Enterprises (SMEs), 2023)
Malawi is a low-income country, despite considerable economic and structural reforms to support economic growth. Agriculture is a major driver of the economy and contributes 36% to national output, generates more than 80% of export earnings, and employs more than 80% of the workforce. The study seeks to identify sectors in Malawi with high growth and employment potential. The study employs the growth identification and facilitation framework, a practical policy instrument operationalizing key insights of new structural economics, to assist policymakers in developing countries in identifying industries and products in which they have a comparative advantage. Using Bangladeshi, China, Rwanda, and Vietnam as comparator countries, the agriculture, manufacturing, and tourism sectors emerge as the development potential of Malawi that can be significantly transformed into competitive advantages. Policy implications emanating from his study include the need for policies that will enhance the business environment and encourage the export of goods and services with added value, especially in the sectors where Malawi has a comparative advantage. Keywords: Comparative Advantage; Economic Growth; Growth Identification and Facilitation Framework; Malawi; New Structural Economics